Reducing patient delay in Acute Coronary Syndrome (RAPiD): research protocol for a web‐based randomized controlled trial examining the effect of a behaviour change intervention. (18th November 2016) - Farquharson, Barbara; Johnston, Marie; Smith, Karen; Williams, Brian; Treweek, Shaun; Dombrowski, Stephan U; Dougall, Nadine; Abhyankar, Purva; Grindle, Mark
Abstract: Aims: To evaluate the efficacy of a behaviour change technique–based intervention and compare two possible modes of delivery (text + visual and text‐only) with usual care. Background: Patient delay prevents many people from achieving optimal benefit of time‐dependent treatments for acute coronary syndrome. Reducing delay would reduce mortality and morbidity, but interventions to change behaviour have had mixed results. Systematic inclusion of behaviour change techniques or a visual mode of delivery might improve the efficacy of interventions. Design: A three‐arm web‐based, parallel randomized controlled trial of a theory‐based intervention. Methods: The intervention comprises 12 behaviour change techniques systematically identified following systematic review and a consensus exercise undertaken with behaviour change experts. We aim to recruit n = 177 participants who have experienced acute coronary syndrome in the previous 6 months from a National Health Service Hospital. Consenting participants will be randomly allocated in equal numbers to one of three study groups: i) usual care, ii) usual care plus text‐only behaviour change technique‐based intervention or iii) usual care plus text + visual behaviour change technique‐based intervention. The primary outcome will be the change in intention to phone an ambulance immediately with symptoms of acute coronary syndrome ≥15‐minute duration, assessed using two randomized series of eight scenarios representing varied symptoms before and after delivery of the interventions or control condition (usual care). Funding granted January 2014. Discussion: Positive results changing intentions would lead to a randomized controlled trial of the behaviour change intervention in clinical practice, assessing patient delay in the event of actual symptoms. Trial registration: Registered at ClinicalTrials.gov: NCT02820103.